E-learning in new normal COVID-19 era: Measure HOTS and pro-environmental behavior about environmental pollution - Ilmi Zajuli Ichsan; Agung Purwanto; Henita Rahmayanti (International Journal of Evaluation and Research in Education (IJERE), 2021)
Current environmental learning amid the COVID-19 new normal situation requires an innovation. This is due to students need various skills to solve environmental pollution issues using Higher Order Thinking Skills (HOTS) and is implemented in the form of Pro-Environmental Behavior (PEB). The innovation is aimed at supporting e-learning utilization. This study aims to delineate university students’ HOTS and PEB and examine the e-learning utilization. Method used in the study is descriptive method using survey technique. Samples involved in the research are 265 university students. The study results indicate that the students’ HOTS score is, overall, in a very low category (31.37). The students’ PEB score, however, is already in a very high position (89.88) as a form to prevent COVID-19 in their surrounding environment. The result of e-learning description suggests that there are still some obstacles in terms of e-learning implementation. The research concludes that the HOTS score is relatively low, whereas the PEB score must be maintained. Suggestions proposed from this study is that to develop teaching materials or learning media, in this context book or supplementary book can be develop, related to environmental pollution as a disaster mitigation effort amid the COVID-19 new normal situation.